Cardiovascular consequences of discontinuing low-dose rivaroxaban in people with chronic coronary or peripheral artery disease - Dagenais, Gilles R; Dyal, Leanne; Bosch, Jacqueline J; Leong, Darryl P; Aboyans, Victor; Berkowitz, Scott D; Bhatt, Deepak L; Connolly, Stuart J; Fox, Keith A A; Muehlhofer, Eva; Probstfield, Jeffrey L; Widimsky, Petr; et al. (Heart, 2021)
OBJECTIVE: In patients with chronic coronary or peripheral artery disease enrolled in the Cardiovascular Outcomes for People Using Anticoagulation Strategies trial, randomised antithrombotic treatments were stopped after a median follow-up of 23 months because of benefits of the combination of rivaroxaban 2.5 mg two times per day and aspirin 100 mg once daily compared with aspirin 100 mg once daily. We assessed the effect of switching to non-study aspirin at the time of early stopping. METHODS: Incident composite of myocardial infarction, stroke or cardiovascular death was estimated per 100 person-years (py) during randomised treatment (n=18 278) and after study treatment discontinuation to non-study aspirin (n=14 068). RESULTS: During randomised treatment, the combination compared with aspirin reduced the composite (2.2 vs 2.9/100 py, HR: 0.76, 95% CI 0.66 to 0.86), stroke (0.5 vs 0.8/100 py, HR: 0.58, 95% CI 0.44 to 0.76) and cardiovascular death (0.9 vs 1.2/100 py, HR: 0.78, 95% CI 0.64 to 0.96). During 1.02 years after early stopping, participants originally randomised to the combination compared with those randomised to aspirin had similar rates of the composite (2.1 vs 2.0/100 py, HR: 1.08, 95% CI 0.84 to 1.39) and cardiovascular death (1.0 vs 0.8/100 py, HR: 1.26, 95% CI 0.85 to 1.86) but higher stroke rate (0.7 vs 0.4/100 py, HR: 1.74, 95% CI 1.05 to 2.87) including a significant increase in ischaemic stroke during the first 6 months after switching to non-study aspirin. CONCLUSION: Discontinuing study rivaroxaban and aspirin to non-study aspirin was associated with the loss of cardiovascular benefits and a stroke excess. TRIAL REGISTRATION NUMBER: NCT01776424.
Keywords: fibrinolytika; ischemická cévní mozková příhoda; Drug Monitoring; Male; Coronary Disease; Aspirin; Duration of Therapy; koronární nemoc; Ischemic Stroke; Mortality; Withholding Treatment; nenasazení léčby; kombinovaná farmakoterapie; Fibrinolytic Agents; Aged; mužské pohlaví; senioři; Drug Therapy, Combination; Peripheral Arterial Disease; onemocnění periferních arterií; trvání terapie; infarkt myokardu; výsledky a postupy - zhodnocení (zdravotní péče); náhrada léků; Rivaroxaban; lidé; ženské pohlaví; Humans; monitorování léčiv; Myocardial Infarction; Outcome and Process Assessment, Health Care; mortalita; Drug Substitution; Female; rivaroxaban